An assessment of web technologies & E-business adoption among SMES travel agencies in Malaysia / Nor Asikin Shaharuddin... [et al.] - Shaharuddin, Nor Asikin; Abd. Rahman, Azmawani; Abd. Aziz, Yuhanis; Kassim, Suhailah (Universiti Teknologi MARA, Negeri Sembilan, 2018)
As the backbone of the economic contributor to the Gross National Profit (GNP), tourism sector plays a vital role in creating employment opportunities. For that reason, attention is given to the travel agencies’ operators to improve productivity and to be competitive in the travel and tour markets. However, in reality, not all companies adopt and use effectively, or even use, information technology. The gap lies between the realities of the actual usage of information technology. A deeper understanding of the current demographic profile and web technologies and e-business adoption practice is vital to know the current trends and practices are implemented among SME entrepreneurs. This study provides a general description of SME’s travel agencies background and web-technology and e-business adoption profile in Malaysia. A total of 313 respondents from SMEs owners/managers has been selected using multistage cluster sampling method to answer the open ended questionnaire. A descriptive analysis SPSS was used in describing the web technologies adoption among Malaysia SMEs travel agencies. The findings of the study revealed that Malaysia SMEs still attach to the conventional way of conducting travel agencyy business.